Formation of metastable phases in magnesium–titanium system by high-pressure torsion and their hydrogen storage performance. (15th October 2015) - Edalati, Kaveh; Emami, Hoda; Staykov, Aleksandar; Smith, David J.; Akiba, Etsuo; Horita, Zenji
Graphical abstract: Abstract: No binary phases exist in the Mg–Ti binary equilibrium phase diagram and the two elements are totally immiscible even in liquid form. This study shows that four metastable phases (two with the bcc and fcc structures and two with the hcp structures) are formed in the Mg–Ti system by severe plastic deformation (SPD) through the process of high-pressure torsion (HPT). Investigation of hydrogenation properties reveals that these metastable phases are decomposed to pure Mg and Ti during heating before they can absorb the hydrogen in the form of ternary Mg–Ti hydrides. First-principles calculations show that the hydrogenation reaction should occur thermodynamically, and ternary Mg–Ti hydrides with the cubic structure should form at low temperature. However, the slow kinetics for this reaction appears to be the limiting step. Calculations show that the binding energy of hydrogen increases and the thermodynamic stability of hydrides undesirably increases by addition of Ti to Mg.